Computer-aiding evaluation of north wall effects of a solar greenhouse: Multiphysics modelling of the indoor environment - L. Zhao; Z. Shui; X. Liu; T. Yang; G. Duan (Case Studies in Thermal Engineering)
The north wall (NW) of a solar greenhouse (SG), oriented away from direct sunlight, plays a crucial role in thermal insulation; however, impacts of the NW internal surface structure (ISS) on the SG indoor environment remains underexplored. Driven by in situ measurements, the temperature (Ti) and relative humidity (RHi) of a SG are evaluated for three typical NW designs: flat wall (FW), striped wall (SW) and alveolate/honeycombed wall (AW). In both sunny and cloudy scenarios, the AW setup ensures a more favourable thermal environment, well aligned with the power spectral analysis indicating enhanced thermal energy capture. The time-lagged cross correlation highlights solar radiation as the primary driver of SG internal thermal variability, with outdoor temperature being of secondary relevance. Additionally, the AW setup consistently maintains the lowest RHi on sunny days, promoting optimal conditions for plant growth, and ensures more stable humidity levels during cloudy nights. The revealed response of SG internal environments to modified NW ISS should offer some insights into SG design, particularly in optimising conditions for plant growth through modifications to the NW structure.